Complex social behaviour derived from maternal reproductive traits - Amdam, Gro V.; Csondes, Angela; Fondrk, M. Kim; Page, Robert E. (Nature, 2006)
Working together On the cover, a solitary bee forages for pollen as a protein-source for her brood alongside a sterile ‘eusocial’ worker honey bee. The social biology of these two females is different, but the evolutionary origin of their behaviour is identical. A eusocial lifestyle involves sterile workers that care for younger siblings. One explanation of how this behaviour arose invokes selection on maternal reproductive traits, and experiments in the honey bee confirm this as a possibility. Intriguingly, differences in worker bee behaviour can be explained by variation in reproductive characteristics. Strains selected to prefer pollen-foraging over nectar-foraging have workers with high, typically unexpressed, reproductive potential. Unselected bees with a high reproductive potential also prefer to collect pollen. This means that maternal traits can act as an evolutionary bridgehead between the solitary estate and worker-containing insect societies. A fundamental goal of sociobiology is to explain how complex social behaviour evolves 1 , especially in social insects, the exemplars of social living. Although still the subject of much controversy 2 , recent theoretical explanations have focused on the evolutionary origins of worker behaviour (assistance from daughters that remain in the nest and help their mother to reproduce) through expression of maternal care behaviour towards siblings 3 , 4 . A key prediction of this evolutionary model is that traits involved in maternal care have been co-opted through heterochronous expression of maternal genes 5 to result in sib-care, the hallmark of highly evolved social life in insects 6 . A coupling of maternal behaviour to reproductive status evolved in solitary insects, and was a ready substrate for the evolution of worker-containing societies 3 , 4 , 7 , 8 . Here we show that division of foraging labour among worker honey bees ( Apis mellifera ) is linked to the reproductive status of facultatively sterile females. We thereby identify the evolutionary origin of a widely expressed social-insect behavioural syndrome 1 , 5 , 7 , 9 , and provide a direct demonstration of how variation in maternal reproductive traits gives rise to complex social behaviour in non-reproductive helpers.